Drought stress does not protect Quercus ilex L. from ozone effects: results from a comparative study of two subspecies differing in ozone sensitivity. (25th July 2013) - Alonso, R.; Elvira, S.; González‐Fernández, I.; Calvete, H.; García‐Gómez, H.; Bermejo, V.; Sparks, J.
Abstract Long‐term effects of ozone (O3) exposure and drought stress were assessed on two subspecies of Quercus ilex: ssp. ilex and ssp. ballota. Two‐year‐old seedlings were continuously exposed for 26 months in open‐top chambers to three O3 treatments: charcoal filtered air, non‐filtered air and non‐filtered air supplemented with 40 nl·l−1 O3. Additionally, two irrigation regimes were adopted: half of the plants were well‐watered and the others received half of the water supplied to control plants. Growth, shoot water potential and gas exchange rates were assessed seasonally, and biomass accumulation was determined at the end of the experiment. Drought stress caused higher reductions of gas exchange, growth and biomass accumulation than O3 exposure in both subspecies. The combination of O3 and drought stress caused further decreases of accumulated aboveground biomass but no additive effects were observed on gas exchange rates or root biomass. Thus, drought stress did not protect Q. ilex from O3 effects on biomass when the response of the whole plant was considered. Q. ilex ssp. ballota was more sensitive to O3 and ssp. ilex was more affected by drought stress. The different O3 sensitivity was not only related to pollutant uptake but also to the ability of plants for resource acquisition and allocation. Based on biomass dose–response functions, Q. ilex is more resistant to O3 than other European evergreen tree species, however, O3 represents an additional stress factor that might be impairing plant ability to withstand current and future climate change.